Geriatric Diseases Evaluation and Management - Nagaratnam, Nages (Springer International Publishing, 2018)
This volume provides a comprehensive overview of the unique clinical entities of diseases in older patients. The book arranges the organ systems in 21 sections, which include over 100 collective chapters on various age-related diseases in these organ systems. The text is specifically designed for ease-of-use and include learning tools that include multiple choice, short answer, and extended matching questions, case vignettes, self-assessments, and rich tables and illustrations. Each section includes a review of the anatomy, physiology and pathology that are specific to aging patients. The text covers the complex factors that present diagnosis challenges, including the interaction of the disease process with co-existing morbidities, aged- related physiological changes and pre-existing functional challenges and psychosocial circumstances. The text also works with the previously published text Diseases in the Elderly: Age-Related Changes and Pathophysiology, which is tailored to complement this resource. Written by experts in the field, Geriatric Diseases: Clinical Expression, Management and Impact is the ultimate guide on clinical expression and management of diseases in the elderly for medical students, residents, fellows, geriatricians, gerontologists, primary care physicians, internal medicine specialists, emergency room physicians, specialist nurses, and all other physicians and medical professionals treating older patients.